TNF-alpha and TNF-beta genes polymorphism in Polish patients with sarcoidosis. Connection with the susceptibility and prognosis - Kieszko, R.; Krawczyk, P.; Chocholska, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Sarcoidosis is a systemic granulomatous disease of unknown aetiology, in which genetic factors, especially the genes of the highly polymorphic MHC region, seem to play an important role in the disease predisposition and course. The aim of this study was to evaluate the role of TNF genes polymorphism in sarcoidosis and to estimate possible association between these polymorphisms and susceptibility and prognosis of sarcoidosis. The analysis of -308G>A TNF-α gene (TNFA*1 and TNFA*2 alleles) and 252A>G TNF-β gene polymorphisms (TNFB*1 and TNFB*2 alleles) were performed. Methods: The study comprised of 130 sarcoidosis patients (75 subjects in the radiological stage I, and 55 in the stages II/III). Löfgren syndrome (LS) was manifested in 38 patients. After at least 3-years observation, 69 patients had remission, 24 subjects manifested persistent disease and 25 patients had progression. The control group consisted of 84 healthy subjects. The genotypes were determined using PCR-RFLP assay. Results: The variant allele TNFA*2 was observed significantly more frequent in patients with Löfgren syndrome when compared to control group (OR=2.301, C.I.=[1.23-4.32], χ2=6.91, p>0.01), as well as to non-LS patients (OR=2.167, C.I.=[1.17-4.01], χ2=6.22, p<0.05).Moreover, the variant allele TNFA*2 was also observed significantly more frequent in patients with disease resolution than in patients with persistent disease and progression (OR=3.53, C.I.=[1.66-7.50], χ2= 11.65, p<0.001).The variant allele TNFA*2 was also overrepresented in patients with disease resolution after exclusion the patients with Löfgren syndrome (OR=2.4, C.I.=[1-5.772], χ2=3.98, p<0.05). There was no significant difference in TNF-A allele distribution between the control group and whole sarcoidosis group. The variant allele TNFB*1 was observed significantly more frequent in patients with disease resolution than in patients with persistent disease and progression. This difference was caused only by overrepresentation of TNFB*1 variant allele in Löfgren group. The significant differences in the distribution of TNFB*1 allele between the sarcoidosis and the control group was also noted (OR=1,607, C.I.=[1,033-2,5], χ2=4.46, p<0.05), but it was limited only to patients displaying Löfgren syndrome. Conclusion: Two alleles TNFB*1 and TNFA*2 of TNF gene are overrepresented in polish patients with Löfgren syndrome. The TNFA*2 allele is related with mild course of sarcoidosis in patients without LS.